-8(a-10)=-8(a-1)+2

Simple and best practice solution for -8(a-10)=-8(a-1)+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8(a-10)=-8(a-1)+2 equation:


Simplifying
-8(a + -10) = -8(a + -1) + 2

Reorder the terms:
-8(-10 + a) = -8(a + -1) + 2
(-10 * -8 + a * -8) = -8(a + -1) + 2
(80 + -8a) = -8(a + -1) + 2

Reorder the terms:
80 + -8a = -8(-1 + a) + 2
80 + -8a = (-1 * -8 + a * -8) + 2
80 + -8a = (8 + -8a) + 2

Reorder the terms:
80 + -8a = 8 + 2 + -8a

Combine like terms: 8 + 2 = 10
80 + -8a = 10 + -8a

Add '8a' to each side of the equation.
80 + -8a + 8a = 10 + -8a + 8a

Combine like terms: -8a + 8a = 0
80 + 0 = 10 + -8a + 8a
80 = 10 + -8a + 8a

Combine like terms: -8a + 8a = 0
80 = 10 + 0
80 = 10

Solving
80 = 10

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 12y(y-3)=15y | | (4x+8)-3=92 | | 6a+4b-9a+5ab-8b= | | 12-(.8)(x+15)=4 | | 8-2x=-3 | | -4+3/2x=/2x | | 8x+11=7x+2 | | 24+12-12=x | | 8(4+8n)+2n=-496 | | -7-3y+2=-8y-8 | | -6(2x+5)=-12x-30 | | -8x+5-2x=-5 | | 5(m+6)=18+7m | | y-1=-3 | | 0=49t+-9.8t | | 25+2x=-7(8x+4)+5x | | 6x-2=7x-8 | | 9p^2-9=891 | | -38=-4+2n | | 15-7x=x-6-5x | | Y-(8-y)=-20 | | 2a+3=-11 | | 15+8-12=x | | 12x+2=3x+11 | | 16x-18+6x+4=118 | | 32+8v=8(7v-2) | | -8=23-5q | | f(x)=5x^2-7x^3 | | -3-6x^2=-103 | | 1+6p=1-p | | 5+a=29 | | (11t-s)(t+5s)= |

Equations solver categories